The accessibility of public spaces for physically disabled people: an analysis of the "Engelsiz Dünya" mobile application as a social responsibility projecp - Kınay, Ömür (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2016)
This study aims to hold a discussion with regards to physically disabled individuals in Turkey in terms of whether or not they can use their most basic rights and freedoms in order to access public spaces, in accordance with the UN Convention on the Rights of Persons with Disabilities as well as other international human rights declarations. The legislative regulations in Turkey with regards to disabled people's physical accessibility to their environments will be cited. Mobile applications aimed for disabled people to access public spaces like every other individual in society, and provide for their basic needs in these public spaces will be mentioned. For example, the usefulness of Vodafone Foundation of Turkey's 2014 "Accessible World" application, in the context of a "social responsibility" project and under the title of "disabled" will be examined. The method that will be used will be the snowball sampling, as a technique not based on probability. An evaluation of mobile applications that were developed thanks to technological developments in order to help disabled people will be made, in parallel with the Human Rights of persons with disabilities that have been developing since the 1940s, but that have picked up pace after the 1990s up until today.
Keywords: Physically Disabled People; Mobile Application; Social Responsibility